Designed zinc finger protein interacting with the HIV-1 integrase recognition sequence at 2-LTR-circle junctions - Supachai Sakkhachornphop (2018)
Integration of HIV-1 cDNA into the host genome is a crucial step for viral propagation. Two nucleotides, cytosine and adenine (CA), conserved at the 3′ end of the viral cDNA genome, are cleaved by the viral integrase (IN) enzyme. As IN plays a crucial role in the early stages of the HIV-1 life cycle, substrate blockage of IN is an attractive strategy for therapeutic interference. In this study, we used the 2-LTR-circle junctions of HIV-1 DNA as a model to design zinc finger protein (ZFP) targeting at the end terminal portion of HIV-1 LTR. A six-contiguous ZFP, namely 2LTRZFP was designed using zinc finger tools. The designed motif was expressed and purified from E. coli to determine its binding properties. Surface plasmon resonance (SPR) was used to determine the binding affinity of 2LTRZFP to its target DNA. The level of dissociation constant (Kd) was 12.0 nM. The competitive SPR confirmed that 2LTRZFP specifically interacted with its target DNA. The qualitative binding activity was subsequently determined by EMSA and demonstrated the aforementioned correlation. In addition, molecular modeling and binding energy analyses were carried out to provide structural insight into the binding of 2LTRZFP to the specific and nonspecific DNA target. It is suggested that hydrogen-bonding interactions play a key role in the DNA recognition mechanisms of the designed ZFP. Our study suggested an alternative HIV therapeutic strategy using ZFP interference of the HIV integration process. Published by Wiley-Blackwell. © 2009 The Protein Society.